Reactive Oxygen Species and Pulmonary Vasculature During Hypobaric Hypoxia - Siques, Patricia; Brito, Julio; Pena, Eduardo (Frontiers in Physiology, 2018)
Abstract An increasing number of people are living or working at high altitudes (hypobaric hypoxia) and therefore suffering several physiological, biochemical and molecular changes. Pulmonary vasculature is one of the main and first responses to hypoxia. These responses imply hypoxic pulmonary vasoconstriction (HPV), remodeling and eventually pulmonary hypertension. These events occur according to the type and extension of the exposure. There is also increasing evidence that these changes in the pulmonary vascular bed could be mainly attributed to a homeostatic imbalance as a result of increased levels of reactive oxygen species (ROS). The increase in ROS production during hypobaric hypoxia has been attributed to an enhanced activity and expression of nicotinamide adenine dinucleotide phosphate-oxidase (NADPH oxidase), though there is some dispute about which subunit is involved. This enzymatic complex may be directly induced by hypoxia-inducible factor-1α (HIF1-α). ROS has been found to be related to several pathways, cells, enzymes and molecules in hypoxic pulmonary vasculature responses, from hypoxic pulmonary vasoconstriction to inflammation, and structural changes, such as remodeling and, ultimately, pulmonary hypertension. Therefore, we performed a comprehensive review of the current evidence on the role of ROS in the development of pulmonary vasculature changes under hypoxic conditions, with a focus on hypobaric hypoxia. This review provides information supporting the role of oxidative stress (mainly ROS) in the pulmonary vasculature´s responses under hypobaric hypoxia and depicting possible future therapeutics or research targets. NADPH oxidase-produced oxidative stress is highlighted as a major source of ROS. Moreover, new molecules, such as ADMA, and critical inflammatory cells as fibroblasts, could be also involved. Several controversies remain regarding the role of ROS and the mechanisms involved in hypoxic responses that need to be elucidated.